ASIAN MINT (MENTHA ASIATICA BORISS) PLANT ESSENTIAL OILS AND ITS CHANGES DEPENDING ON VEGETATIVE PHASES - Kh.K. Djumaev; J.U. Khushvaktov; I.I. Nosirjonov (Journals Park Publishing, 2022)
Essential oils were extracted from different organs of Asian mint - Mentha asiatica Boriss. It was found that there are 0.10% of essential oils in the aerial part of plants in the vegetative phase, 0.13% in the leaves, 0.14% in the aerial part of the flowering phase, 0.17% in the leaves and 0.23% in the flowers (calculated as % wet mass).
Keywords: Asiatic mint, Mentha asiatica Boriss., essential oil plants, Ginzberg apparatus